Why is basic service access worse in slums? A synthesis of obstacles. Issue 3 (3rd April 2017) - Pierce, Gregory
ABSTRACT: Many residents of urban areas face joint obstacles to basic service access, but these barriers are more prevalent and severe in slum settlements. Analyses of obstacles have typically been conducted in a piecemeal rather than synthetic framework and have focused on access to single services rather than the range of services needed to support household welfare. By contrast, this study uses data from fieldwork in four slum settlements situated in Hyderabad, India to develop a typology synthesising the obstacles – economic, spatial, social, institutional, and political – to the full range of service access desired by residents. Economic differences explain little of the access deficit within this population. While social and institutional obstacles are more likely to explain slum formation and residence over the long term, variation in spatial and political factors present the most acute short-term access barriers. The article concludes by suggesting the most promising means for slum residents and supporting stakeholders to overcome multi-faceted obstacles.